Pediatric N-Methyl-d-Aspartate Receptor Encephalitis is Differentiated From Encephalitis Mimickers by Early Elevated Blood Pressure - Kass, Naomi R.; Ledbetter, Elizabeth; Erickson, Timothy A.; Yarimi, Jonathan M.; Zoghbi, Anthony; Muscal, Eyal; Murray, Kristy O.; Fisher, Kristen S.; Sandweiss, Alexander J. (Pediatric neurology, 2025)
Pediatric N-methyl-d-aspartate receptor (NMDAR) encephalitis (pNMDARE) is characterized by severe neuropsychiatric symptoms and prolonged hospitalization and recovery. Early pNMDARE diagnosis is complicated by neuropsychiatric mimickers requiring strong clinical suspicion to escalate to the required lumbar puncture (LP), delaying diagnosis and treatment. Since autonomic dysfunction is a cardinal feature of pNMDARE, we hypothesized that early vital signs serve as a potential noninvasive biomarker to screen for appropriate escalation of pNMDARE evaluation. This is a retrospective, case-control analysis of patients with pNMDARE between 2021 and 2023. Patients diagnosed with pNMDARE as determined by clinical presentation and positive cerebrospinal fluid (CSF) antibodies (Abs) were compared with control subjects who were evaluated for pNMDARE, including an LP, but were negative. Fifty-seven patients were included for analysis: 23 diagnosed with pNMDARE and 34 without. When standardized for age, sex, and height, the pNMDARE group had higher systolic and diastolic BP percentiles (BP%ile) compared with the anti-NMDAR Ab–negative group (systolic BP%: 95.0% ± 2.3% vs 68.8% ± 4.4%, respectively, P < 0.001; diastolic BP%: 88.3% ± 2.8% vs 61.3% ± 4.1%, respectively; P < 0.001). A receiver operator curve indicated that the shortest Euclidian distance for systolic BP%ile was 99th%ile (specificity, 85.3%; sensitivity, 65.2% P < 0.0001) and for diastolic BP%ile was 88.5th%ile (specificity, 73.5%; sensitivity, 65.2%; P < 0.005). Although CSF Ab is required for the diagnosis of pNMDARE, screening tools may help hasten clinical suspicion for the need for an LP. We identified elevated BP as a potential differentiating early clinical marker specific to pNMDARE. This fact corroborates our current understanding of dysautonomia in pNMDARE and provides a potential clinical marker suitable for future research and validation.